Inventory Management System for SMEs in Kulim / Muhammad Bilal Hakim Azmi and Muhammad Nabil Fikri Jamaluddin - Azmi, Muhammad Bilal Hakim; Jamaluddin, Muhammad Nabil Fikri (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Small to medium size companies tend to face problems with the tracking of their inventory which could lead to losses for the company. The Inventory Management System for SMEs in Kulim is developed to allow the user to improve the inventory management using a computerised system. The system has a function where users can update their inventory list in different pages such as brand, category and products. It is easy for the users to monitor their inventory anywhere with internet access since the system is built as a web-based application. Admin are the only user with the access to manage the inventory thus, it is easy for them to handle the system without the interference from the third party. Functions such as add, delete or update can be done for all the categories listed above. This project was evaluated by distributing questionnaires to 30 respondents which contained questions from user acceptance testing. Respondents are free to test the system and evaluate based on their experience.